Accelerated Aging in HIV/AIDS: Novel Biomarkers of Senescent Human CD8+ T Cells - Chou, Jennifer P.; Ramirez, Christina M.; Wu, Jennifer E.; Effros, Rita B. (PloS one, 2013)
Clinical evaluation of immune reconstitution and health status during HIV-1 infection and anti-retroviral therapy (ART) is largely based on CD4+ T cell counts and viral load, measures that fail to take into account the CD8+ T cell subset, known to show features of accelerated aging in HIV disease. Here, we compare adenosine deaminase (ADA), glucose uptake receptor 1 (GLUT1), and leucine-rich repeat neuronal 3 (LRRN3) to CD38 expression and telomerase activity, two strong predictors of HIV disease progression. Our analysis revealed that reduced ADA, telomerase activity and LRRN3 gene expression were significantly associated with high CD38 and HLA-DR in CD8+ T cells, with % ADA+ cells being the most robust predictor of CD8+ T cell activation. Our results suggest that ADA, LRRN3 and telomerase activity in CD8+ T cells may serve as novel, clinically relevant biomarkers of immune status in HIV-1 infection, specifically by demonstrating the degree to which CD8+ T cells have progressed to the end stage of replicative senescence. Since chronological aging itself leads to the accumulation of senescent CD8+ T cells, the prolonged survival and resultant increased age of the HIV+ population may synergize with the chronic immune activation to exacerbate both immune decline and age-associated pathologies. The identification and future validation of these new biomarkers may lead to fresh immune-based HIV treatments.